DEVELOPMENT OF BILAYER TABLETS FOR IMMEDIATE AND CONTROLLED RELEASE OF ALLICIN - Das, Manoj Kr.; Sahu, Bhanu P.; Hazarika, Jahan Nur Rahman (International Journal of Current Pharmaceutical Research, 2017)
Objective: The purpose of this study was to develop and evaluate bilayer tablet for the immediate and controlled release of Allicin (Garlic Extract) for effective treatment of Hypertension. Methods: The immediate release layer was prepared by using super disintegrants-sodium starch glycolate and binder used xantham gum and the sustained release layer was prepared by using hydrophilic polymer like HPMC K 100 and PVP. Before preparation of the tablets, all the pre-formulation parameters were checked and the tablet of Allicin were prepared by direct compression method and was evaluated for physical characteristics like hardness, weight variation, drug content and friability. In vitro release of drug was performed USP type II dissolution test apparatus using phosphate buffer (pH 7.4) as dissolution media and dissolution was continued for 8 hrs for the sustained release layer. Results: It was found that all the formulations were within the limit of the standard. The drug release of the tablet was in the range of 66%-83% in 8 h. Conclusion: It was concluded that the F4 formulation showed the optimum result as a bilayer tablet for the effective treatment of hypertension. Â